The level of electromagnetic radiation from mobile phones - Матоушек, З.; Якуб, Й.; Шостронек, М. (Proceedings of National Aviation University (archive), 2009)
Mathematical approach for analysis of measurement of electromagnetic fields from mobile telephones and its in fluence on human body is considered in the article.